2020
DOI: 10.1108/pr-12-2019-0688
|View full text |Cite
|
Sign up to set email alerts
|

Social exchange and psychological ownership as complementary pathways from psychological contract fulfillment to organizational citizenship behaviors

Abstract: PurposeSocial comparison and job-based psychological ownership (JPO) are compared and contrasted as explanations for relationships between organization relational psychological contract fulfillment (ORPCF) and organizational citizenship behaviors (OCBs).Design/methodology/approachSurvey data were collected from 241 employees and 82 of their managers at an information services company. Data were analyzed using structural equation modeling to test for hypothesized and exploratory indirect relationships.FindingsC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…In relation to the behavioral effects of psychological ownership, our findings concur with previous findings (Brown, 1989;Gardner et al, 2020) that psychological ownership can have a positive impact on employee behavior. We find that psychological ownership for the job is positively associated with work engagement (β = .22, p < .05).…”
Section: Major Findings and Theoretical Implicationssupporting
confidence: 91%
“…In relation to the behavioral effects of psychological ownership, our findings concur with previous findings (Brown, 1989;Gardner et al, 2020) that psychological ownership can have a positive impact on employee behavior. We find that psychological ownership for the job is positively associated with work engagement (β = .22, p < .05).…”
Section: Major Findings and Theoretical Implicationssupporting
confidence: 91%
“…The sense of possession also affects personal attitudes and behaviors [18]. This target of ownership would result in providing a more complete explanation for sustained positive behaviors [20]. In the organizational context, psychological ownership can be a critical predictor of employees' attitudes, behaviors, and performance [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…It is also posited that, while negative triggers in an organisation can cause the negative reaction of defensive voice from an employee, positive triggers in an organisation [such as positive organisational behaviour (POB) of PO experienced towards job or organisation (Avey et al, 2009)] may mitigate the negative reaction of defensive voice from an employee. On examining the extant literature on the relationship between different predictors and defensive voice (Bharanitharan et al, 2019;Lu et al, 2019;Ng et al, 2021), and the relationship between PO (experienced towards job or organisation) and positive employee voice (Andiyasari et al, 2017;Gardner et al, 2021;Mustafa et al, 2015;O'Driscoll et al, 2006;Ramos et al, 2014;Wang et al, 2019), it was identified that the relationships between PO (organisation-based) and negatively-intended defensive voice to supervisor and between PO (job-based) and negatively-intended defensive voice to supervisor are not examined in existing literature. This research gap is examined in hypotheses 1 and 2 (associated with RQ1) discussed below.…”
Section: Psychological Ownership and Defensive Voice To Supervisormentioning
confidence: 99%